The Influence of Price and Company Image on Ticket Purchase Decisions at the Medan X Beauty Event at Santika Premiere Dyandra 2024 - Hutabarat, Hatop Martaban; Surbakti, Enda Yunita (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to analyze the effect of price and corporate image on the purchase decision of Medan X Beauty tickets. The background of the research is based on the increasing competition in the beauty event industry, making pricing strategy and corporate image important factors in attracting consumer interest. This study employed a quantitative method with multiple linear regression analysis. The sample consisted of 100 respondents selected using the purposive sampling technique.The analysis results show that, partially:The price variable has a positive and significant effect on purchase decision with t = 4.021 > 1.984 and Sig. = 0.001 < 0.05.The corporate image variable has a positive and significant effect with t = 5.035 > 1.984 and Sig. = 0.001 < 0.05.Simultaneously, price and corporate image have a positive and significant effect on purchase decision with F-value = 106.569 > F-table = 3.09 and Sig. = 0.001 < 0.05. The coefficient of determination (R² = 0.687) indicates that 68.7% of the variation in purchase decisions is explained by price and corporate image, while the remaining 31.3% is influenced by other variables outside this study. Therefore, it can be concluded that the corporate image factor is more dominant in influencing the purchase decision of Medan X Beauty tickets compared to the price factor. The findings of this research are expected to serve as a consideration for event management in determining effective marketing strategies.